Integrating blue: How do we make nationally determined contributions work for both blue carbon and local coastal communities? - Amrit Melissa Dencer-Brown; Robyn Shilland; Daniel Friess; Dorothée Herr; Lisa Benson; Nicholas J. Berry; Miguel Cifuentes-Jara; Patrick Colas; Ellyn Damayanti; Elisa López García; Marina Gavaldão; Gabriel Grimsditch; et al. (Ambio, 2022)
Blue Carbon Ecosystems (BCEs) help mitigate and adapt to climate change but their integration into policy, such as Nationally Determined Contributions (NDCs), remains underdeveloped. Most BCE conservation requires community engagement, hence community-scale projects must be nested within the implementation of NDCs without compromising livelihoods or social justice. Thirty-three experts, drawn from academia, project development and policy, each developed ten key questions for consideration on how to achieve this. These questions were distilled into ten themes, ranked in order of importance, giving three broad categories of people , policy & finance , and science & technology . Critical considerations for success include the need for genuine participation by communities, inclusive project governance, integration of local work into national policies and practices, sustaining livelihoods and income (for example through the voluntary carbon market and/or national Payment for Ecosystem Services and other types of financial compensation schemes) and simplification of carbon accounting and verification methodologies to lower barriers to entry.

Nidogen 1 and Nuclear Protein 1: novel targets of ETV5 transcription factor involved in endometrial cancer invasion - Núria Pedrola; Laura Devis; Marta Llauradó; Irene Campoy; Elena Martinez-Garcia; Marta Garcia; Laura Muinelo-Romay; Lorena Alonso-Alconada; Miguel Abal; Francesc Alameda; Gemma Mancebo; Ramon Carreras; et al. (Clinical & Experimental Metastasis, 2015)